A Study Review of Coconut Shells as Replacement for Coarse Aggregate - Noorasmawanty binti Daud,; Norfaniza Binti Mokhtar, (Recent Trends in Civil Engineering and Built Environment, 2022)
Concrete is most commonly used structural material in the construction sector is concrete. The increasing of concrete used also contributes to the massive demand for coarse aggregate. In order to follow the sustainable development of society, coconut shells can also be used as a coarse aggregate replacement material. The objectives of this study is to investigate the effectiveness of coconut shell as coarse aggregate replacement on engineering properties such as strength, water absorption and workability on concrete based on previous research and to observe the influence of the coconut shell inclusion in concrete on the microstructural characteristics. By critical review, this study found that concrete with coconut shell shows a positive impact on the workability of concrete and water absorption but for the compressive strength. The percentage of replacement of 0% - 30% influence an improvement of concrete on the workablity and water absorption but the negative effect on compressive strength. The microstructural characteristic of coconut shell in concrete also give positive influence in concrete using scanning electron microscopy (SEM) and X-ray diffraction (XFD), with pore structure that acts as storage, indicating that the bond between the coconut shell and cement is stronger, and that the compounds of coconut shell in concrete have a significant positive influence on the strength of the concrete.After considering all factor based on analysis, about 20% to 25% of replacement are suitable to replace coarse aggregate.